2017
DOI: 10.12688/f1000research.11523.1
|View full text |Cite
|
Sign up to set email alerts
|

Advances on minimally invasive approach for benign total hysterectomy: a systematic review

Abstract: Hysterectomy is one of the most commonly performed gynecologic surgeries, mainly for uterine myomas, abnormal uterine bleeding, and prolapses. It can be performed through several routes, each of which has its advantages and disadvantages. We conducted this systematic review to evaluate recent advances in surgical outcomes of benign total hysterectomies by any route: vaginal (VH), laparoscopic (LH), laparoscopically assisted vaginal (LAVH), single-port (SP), and robotic-assisted laparoscopy (RH). The search was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
2
8
0
1
Order By: Relevance
“…In a study by Simpson et al, it is underlined that there were differences regarding the opinions on the benefits of robotic surgery between the users and the literature [19]. In an article by Andres et al, robotic surgery in benign uterine diseases was not found to be superior to other classic methods [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Simpson et al, it is underlined that there were differences regarding the opinions on the benefits of robotic surgery between the users and the literature [19]. In an article by Andres et al, robotic surgery in benign uterine diseases was not found to be superior to other classic methods [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the most conclusive studies the recommendations for deciding on what is the best approach are based on health outcomes and healthcare costs without taking into account indirect costs, which should be an important fact for decision making. 2,3,15 To our knowledge, this study represents the most expansive analysis of costs associated with LH and VH for benign disease. Most comparative studies on hysterectomy are based on hospitalization cost 8,16,17 and the most important contribution of this study is the consideration of the indirect cost mainly represented by transport and lostwork-productivity costs.…”
Section: Introductionmentioning
confidence: 99%
“…Hysterectomy for patients with uterine leiomyomas is one of the most common gynecological surgeries [ 1 ], and all gynecologists in local private clinics and major regional or university hospitals often encounter these patients. Recently, less invasive technologies, including laparoscopic hysterectomy and other cutting-edge methods, have come to be the mainstream treatments [ 2 ]; however, the hard and soft capacities required are not necessarily available in all hospitals.…”
Section: Introductionmentioning
confidence: 99%